If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 8) = 2(2x + 40) Reorder the terms: 3(8 + 2x) = 2(2x + 40) (8 * 3 + 2x * 3) = 2(2x + 40) (24 + 6x) = 2(2x + 40) Reorder the terms: 24 + 6x = 2(40 + 2x) 24 + 6x = (40 * 2 + 2x * 2) 24 + 6x = (80 + 4x) Solving 24 + 6x = 80 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 24 + 6x + -4x = 80 + 4x + -4x Combine like terms: 6x + -4x = 2x 24 + 2x = 80 + 4x + -4x Combine like terms: 4x + -4x = 0 24 + 2x = 80 + 0 24 + 2x = 80 Add '-24' to each side of the equation. 24 + -24 + 2x = 80 + -24 Combine like terms: 24 + -24 = 0 0 + 2x = 80 + -24 2x = 80 + -24 Combine like terms: 80 + -24 = 56 2x = 56 Divide each side by '2'. x = 28 Simplifying x = 28
| 10x-7y=44 | | 5+2(x+3)=-x-6 | | 0=t^2+t-6 | | a+5=-16 | | -3(5+7p)=33-5p | | -2(x+7)=4x-7 | | -4=13.7 | | 15-3x=12-5x | | 4w(w-6)-2w^2=2w^2+8w-4 | | 2+3n=0.8n+18 | | 14-x=3x-2 | | x^3+5x^2+16x+80=0 | | 4/28=x/147 | | -7(x-6)-8=-5x+40 | | 5W+W=36 | | h=9(8m-9r) | | 6(-6-5)-6=0 | | ln(x+11)+ln(x-3)=2lnx | | 0=a^2-18a+72 | | 4x+6=-7x-7 | | -15t^2+60t=0 | | 5t+6-8t=30 | | 24t^2+19t+2=0 | | .25p+7=3 | | (2x^2-5x-3)=0 | | 2q+30=6-4q | | 50x=20x+10 | | 3x+5+6x=113 | | 50x=20x+30 | | x-2+25=66-2+3x | | 6p-2(p+6)=20 | | 0.5d-8=3 |